2018
DOI: 10.1016/j.apenergy.2018.01.033
|View full text |Cite|
|
Sign up to set email alerts
|

Kinetic studies on organic degradation and its impacts on improving methane production during anaerobic digestion of food waste

Abstract: Organics degradation is vital for food waste anaerobic digestion performance, however, the influence of organics degradation on biomethane production process has not been fully understood. This study aims to thoroughly investigate the organics degradation performance and identify the interaction between the reduction of organic components and methane yield based on the evaluation on 12 types of food waste. Five models (i.e.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 46 publications
1
32
1
1
Order By: Relevance
“…There was no lag-phase for the activated sludge to indicate successful adaptation of the microorganism to the wastewater, or the acclimatization condition of the activated sludge was sufficient to decompose organic substances. It indicates that the soluble mate-rial in the liquid phase of the substrates was quickly consumed by the anaerobic microorganisms [16]. Food-grade waste is characterized as having high degrees of readily degradable materials as well as digestibility.…”
Section: Performance Of Compartmentsmentioning
confidence: 99%
“…There was no lag-phase for the activated sludge to indicate successful adaptation of the microorganism to the wastewater, or the acclimatization condition of the activated sludge was sufficient to decompose organic substances. It indicates that the soluble mate-rial in the liquid phase of the substrates was quickly consumed by the anaerobic microorganisms [16]. Food-grade waste is characterized as having high degrees of readily degradable materials as well as digestibility.…”
Section: Performance Of Compartmentsmentioning
confidence: 99%
“…The highest SI-ratios (0.4 for sludge and 0.7 for manure) correspond to the slowest growth rate. When comparing the results of the three mathematical models, transference functions showed higher values for µm and λ for sludge assays, such as in the experiments carried out by Li et al (2018) digesting food wastes with seed sludge. In the present experiment, the transference function of manure assays showed lower µm and λ values.…”
Section: Kinetic Studymentioning
confidence: 98%
“…Figure 2 shows examples of typical cumulative biogas and methane yields. The evaluation of the BMP curves can be aided by mathematical models of methane production kinetics (El-Mashad 2013, Dong et al 2016, Ware and Power 2017, Yangyang et al 2018.…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…The short lag phase conveys that the soluble material in the substrate was rapidly disposed of by the anaerobic microorganisms [40]. Y. Li et al [17] reported a lag phase of 0.05 days to 0.52 days using modified Gompertz modelling suggested that a short lag phase for the biodegradation of the total solid.…”
Section: Kinetics Of Methane Productionmentioning
confidence: 99%
“…However, simulation of the model and the discontinuous anaerobic digestion performed previously were predominantly in accordant with first-order or modified Gompertz models [16]. The first-order models known as the simplest model was applied to estimate the parameter, to improve the understanding of the biological process and predict the behaviour of the biological system in developing the anaerobic system [17]. The modified Gompertz model has been adopted to analyse the production of methane from batch experiments [18,19].…”
Section: Introductionmentioning
confidence: 99%